2020
DOI: 10.1101/2020.12.30.424814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Land-use and forest floor explain prokaryotic metacommunity structuring and spatial turnover in Amazonian forest-to-pasture conversion areas

Abstract: Advancing extensive cattle production shifts the forest landscape and is considered one of the main drivers against biodiversity conservation in the Brazilian Amazonia. Considering soil as an ecosystem it becomes vital to identify the effects of land-use changes on soil microbial communities, structure, as well as its ecological functions and services. Herein, we explored relationships between land-use, soil types and forest floor (i.e., association between litter, root layer and bulk soil) on the prokaryotic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…1) and consequent loss in pairwise beta diversities (Fig. 2), which is indicative of biotic homogenization (Rodrigues et al 2013;Maaß et al 2014;Rocha et al 2021). These results corroborate our previous study, in which we evaluated, through metagenomics, the patterns of microbial alpha and beta diversities in two out of six counties evaluated here (Goss-Souza et al 2017).…”
Section: Drivers Of Bacterial Assembly Patterns and Processes Across ...mentioning
confidence: 99%
See 1 more Smart Citation
“…1) and consequent loss in pairwise beta diversities (Fig. 2), which is indicative of biotic homogenization (Rodrigues et al 2013;Maaß et al 2014;Rocha et al 2021). These results corroborate our previous study, in which we evaluated, through metagenomics, the patterns of microbial alpha and beta diversities in two out of six counties evaluated here (Goss-Souza et al 2017).…”
Section: Drivers Of Bacterial Assembly Patterns and Processes Across ...mentioning
confidence: 99%
“…While generalists follow the Baas Becking theory of "everything is everywhere" (De Wit and Bouvier 2006), habitat specialists are the microorganisms that have restricted occupancy, as represented by their low occurrence across environmental and geographical gradients (Meyer et al 2018;Gao et al 2019;Ceola et al 2021). The competitive/cooperative interactions among microbial populations in a local community (Li et al 2018) and sets of metapopulations in metacommunity (Hovatter et al 2011;Rocha et al 2021) are very intricate (Leibold et al 2004) and land-use change can greatly alter the role of these interactions in microbial community assembly (Creamer et al 2016;Brinkmann et al 2019;Goss-Souza et al 2020). Some authors have found land-use change and management intensification in tropical soils, as selective abiotic filters, by increasing the competition among species for habitat and limiting resources, according to niche (Mendes et al 2014;Goss-Souza et al 2019).…”
Section: Introductionmentioning
confidence: 99%